AL-ASĀLĪB AL-BADĪ‘IYYAH FĪ KITĀB "NAWĀBIGH AL-KALIM" LI AL-ZAMAKHSHARĪ: DIRĀSAH TAḤLĪLIYYAH BALĀGHIYYAH - Uthman Idrees Kankawi (Journal of Arabic Literature (JaLi), 2024)
This study investigates the rhetorical patterns in Nawābighul-Kalim by Zamakhshari, a literary work composed after the author reached the age of 42 in the eighth-century Hijri. The book contains richly embellished expressions that reflect his personal experiences and are intended as sources of wisdom and moral instruction. The primary aim of this research is to examine selected themes from the text and identify the rhetorical techniques employed. Although Nawābighul-Kalim has received considerable scholarly attention in the domain of grammatical analysis, little has been done to explore its rhetorical depth. To address this gap, the study adopts a retrieval method for documenting historical facts about the author, an inductive method for identifying rhetorical features, and a descriptive approach for analysing selected themes. The findings reveal the use of diverse rhetorical devices, including assonance, alliteration, antithesis, analogy, euphemism, twist, and distribution. This research, titled "Figurative Styles in Nawābighul-Kalim by Zamakhshari: A Rhetorical Analytical Study," highlights the author's artistic and rhetorical mastery while also drawing attention to the significance of the work within scholarly and academic contexts, particularly its inclusion in higher education curricula.